2018
DOI: 10.1186/s12889-018-6042-0
|View full text |Cite
|
Sign up to set email alerts
|

Examining subgroup effects by socioeconomic status of public health interventions targeting multiple risk behaviour in adolescence

Abstract: BackgroundMultiple risk behaviour (MRB) refers to two or more risk behaviours such as smoking, drinking alcohol, poor diet and unsafe sex. Such behaviours are known to co-occur in adolescence. It is unknown whether MRB interventions are equally effective for young people of low and high socioeconomic status (SES). There is a need to examine these effects to determine whether MRB interventions have the potential to narrow or widen inequalities.MethodsTwo Cochrane systematic reviews that examined interventions t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
22
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 141 publications
1
22
0
Order By: Relevance
“…Generally, individuals with a lower socioeconomic position are more likely to start smoking in adolescence and less likely to quit smoking in adulthood [ 1 , 2 ]; thus, contributing to social disparities in smoking and in health. An increasing priority of smoking preventive measures is to equalize socioeconomic disparities in smoking [ 3 , 4 ]. However, these efforts might be challenged because health interventions are sometimes easier adopted by individuals from higher socioeconomic backgrounds [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…Generally, individuals with a lower socioeconomic position are more likely to start smoking in adolescence and less likely to quit smoking in adulthood [ 1 , 2 ]; thus, contributing to social disparities in smoking and in health. An increasing priority of smoking preventive measures is to equalize socioeconomic disparities in smoking [ 3 , 4 ]. However, these efforts might be challenged because health interventions are sometimes easier adopted by individuals from higher socioeconomic backgrounds [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…A particular strength of this study is the collaborative approach involving researchers from various relevant disciplines, including (social) epidemiologists, statisticians, health psychologists, primary care and public health researchers, as well as human movement scientists. Going beyond other projects on equity-specific re-analyses [29,32,39], the jointly developed re-analysis strategy includes harmonizing the definitions of exposure and outcome measures, the choice and definition of indicators of social inequalities, as well as modeling strategies across studies as much as possible. The collaboration procedure, comprising regular exchange via e-mail, Skype, and face-to-face meetings, further bears the advantages of discussing methodological issues, analysis findings, and implications for the future development of social inequalities-sensitive interventions.…”
Section: Discussionmentioning
confidence: 99%
“…However, due to limited resources, most studies are not prospectively designed with sufficient power to examine effects in subgroups which may limit credibility of equity-specific findings [28]. Although insufficient statistical power is a valid reason for not to conduct or report such equity-specific analyses, the importance of understanding how interventions affect health inequalities make re-analyzing intervention studies by indicators of social inequalities a potentially valuable approach [29,30,31,32,33]. As this requires access to and analyses of primary data, a collaborative approach involving authors and researchers of the primary studies is necessary.…”
Section: Introductionmentioning
confidence: 99%
“…Previous research has shown that HED is associated with increased aggression and fighting [ 5 ]. This compounding of alcohol with violence has major public health and safety consequences in adolescents and young adults, and a focus of many alcohol prevention programs worldwide in these younger age groups [ 49 , 50 ].…”
Section: Discussionmentioning
confidence: 99%